Effect of Roy’s Adaptation Theory- Based Mindfulness Therapy on Work Stress: A Quasy-Experimental Study - Isidorus juri Dwi Aprianto; Blacius Dedi; Indah Wulaningsih (An Idea Health Journal, 2026)
Background:Work-related stress among inpatient nurses represents a significant occupational health concern that adversely affects psychological well-being, job performance, and quality of patient care. Despite increasing evidence supporting mindfulness-based interventions, their integration within a nursing theoretical framework remains limited. This study aimed to examine the effect of mindfulness therapy grounded in the Roy Adaptation Model on work-related stress among inpatient nurses in a private hospital in Semarang, Indonesia Methods: A quasi-experimental two-group pretest–posttest design was employed. Sixty nurses were recruited using purposive sampling and assigned to an intervention group (n = 30) and a control group (n = 30). Result: Work-related stress was measured using the Job Stress Scale, which demonstrated excellent internal consistency (Cronbach’s α = 0.965). Higher scores indicated lower levels of stress. The intervention group received mindfulness therapy three times per week for two weeks.The mean stress score in the intervention group increased significantly from 51.87 ± 2.97 at baseline to 78.87 ± 2.98 after the intervention (p < 0.001), indicating a substantial reduction in stress levels, with a very large effect size (Cohen’s d = 28.51). No significant change was observed in the control group (p = 0.161). Conclusion: These findings indicate that mindfulness therapy based on the Roy Adaptation Model effectively enhances adaptive coping mechanisms and significantly reduces work-related stress among inpatient nurses.